Augmented Reality Traditional Dance, Integrating into Students' Cultural Literacy - Shinta Fierda Kus Edwin; Dinny Devy Triana; Elindra Yetti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research discusses the application of Augmented Reality (AR) technology in teaching traditional dance as a means of increasing the cultural literacy of junior high school students. The research aims to overcome the lack of students' understanding of traditional dance due to the lack of direct interaction with these cultural practices. The research method used a qualitative case study approach. The case study was chosen because it allows researchers to intensively explore the dynamics of learning in a limited context, namely at SMPN 13 Jakarta, and produce a comprehensive understanding of the role of AR technology in building cultural literacy. The results showed that the use of AR in traditional dance learning significantly increased students' interest, participation, and understanding of the cultural values contained in dance. In conclusion, the integration of AR technology in cultural arts learning provides a new alternative in shaping learning that is more contextual, collaborative, and oriented towards strengthening character and local cultural values. This research recommends expanding the use of AR media not only in dance, but also in other cultural arts fields such as music, visual arts, and theater.